RANCANGAN PELAPORAN REKONSILIASI PROHIBITED ITEMS PADA HB-SCP BERBASIS APPSHEET DALAM MENDUKUNG KEAMANAN DI BANDAR UDARA KALIMARAU - Zidan Mushajid; Nawang Kalbuana; Irwan Faizal (FTK UNSURYA, 2026)
Ensuring security in airports is essential, especially in overseeing passenger luggage. However, at Kalimarau Airport, the current manual method of reporting seized items increases the risk of inaccuracies and processing delays. This research focuses on designing a reconciliation reporting system for confiscated items based on the AppSheet application connected to an online database. The methodology includes needs analysis, digital reporting system design, and field testing. The application supports real-time recording, data visualization, and report automation. Testing results indicate improved efficiency and accuracy in recording, with a system feasibility rating above 90% based on expert evaluation and user trials. In conclusion, this reporting system is deemed suitable as a digital solution for managing confiscated items at airports, enhancing transparency, speed, and data security.